Pengamanan Kunci Pintu Brankas Menggunakan Kriptografi One Time Pad (OTP) Berbasis Android - Munjiat Setiani Asih; Ade Zulkarnain Hasibuan (Explorer, 2023)
A safe is a place used to store valuable items. Generally, safes use buttons to open the door. However, using buttons that only require entering a password is considered less secure. Therefore, a device has been created to enhance the security of the entered password. The device utilizes Arduino as the central data processing unit for user input and an Android smartphone as the device for entering the password. The security is implemented using the cryptographic technique known as One Time Pad, where the user is prompted to input the password to be used. During the password storage process, the password is encrypted before being stored. To use it, the user simply enters the stored password into the system. If the device is forcefully tampered with, a thief attempting to retrieve the password will be unable to understand the stored password within the device, as it has undergone encryption. With this dual security measure in place, it is expected that the safe will be even more secure.